Bosnia and Herzegovina : Financial Sector Assessment Program-Detailed Assessment of Observance of the CPMI-IOSCO Principles for Financial Market Infrastructures. - International Monetary Fund. Monetary and Capital Markets Department (Washington, D.C. : International Monetary Fund, 2015)
This paper discusses key findings and recommendations of the Detailed Assessment of Observance of the CPMI-IOSCO (Committee on Payments and Market Infrastructures-International Organization of Securities Commissions) Principles for Financial Market Infrastructures in Bosnia and Herzegovina. Major achievements have been made in modernizing the payment system. Resiliency of the interbank payment system was demonstrated against the severe floods of May 2014. The currency board arrangement has helped protect the payment system from credit risks. The formal assessment of the real-time gross settlement system suggests that many of the standards are observed. The legal basis is relatively sound, but finality and netting arrangements require greater legal certainty and protection at the law level.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet